2022
DOI: 10.3389/fpls.2022.841464
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Functional Traits of Two Species Affected by Nitrogen Addition Rate and Period Not Nitrogen Compound Type in a Meadow Grassland

Abstract: Plasticity of plant functional traits plays an important role in plant growth and survival under changing climate. However, knowledge about how leaf functional traits respond to the multi-level N addition rates, multiple N compound and duration of N application remains lacking. This study investigated the effects of 2-year and 7-year N addition on the leaf functional traits of Leymus chinensis and Thermopsis lanceolata in a meadow grassland. The results showed that the type of N compounds had no significant ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…In the study, the LNC of both species showed susceptibility in response to different N addition levels. This result is consistent with previous findings wherein long-term N addition enhanced remarkably the leaf N concentration in the plant dominant species ( Broadbent et al, 2020 ; Khan et al, 2020 ; Sun et al, 2022 ). Previous studies suggest that most species increased in SLA and declined in LDMC with the addition of N ( Tatarko and Knops, 2018 ; Sun et al, 2022 ); however, the SLA, LDMC, and LCC of the two species did not respond to the N addition, and the reason for inconsistency with previous findings may be due to species-specific.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the study, the LNC of both species showed susceptibility in response to different N addition levels. This result is consistent with previous findings wherein long-term N addition enhanced remarkably the leaf N concentration in the plant dominant species ( Broadbent et al, 2020 ; Khan et al, 2020 ; Sun et al, 2022 ). Previous studies suggest that most species increased in SLA and declined in LDMC with the addition of N ( Tatarko and Knops, 2018 ; Sun et al, 2022 ); however, the SLA, LDMC, and LCC of the two species did not respond to the N addition, and the reason for inconsistency with previous findings may be due to species-specific.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with previous findings wherein long-term N addition enhanced remarkably the leaf N concentration in the plant dominant species ( Broadbent et al, 2020 ; Khan et al, 2020 ; Sun et al, 2022 ). Previous studies suggest that most species increased in SLA and declined in LDMC with the addition of N ( Tatarko and Knops, 2018 ; Sun et al, 2022 ); however, the SLA, LDMC, and LCC of the two species did not respond to the N addition, and the reason for inconsistency with previous findings may be due to species-specific. The traits of the two species were differentially responsive to N addition, LDMC and LCC of S. glareosa were consistently higher than those of P. harmala , and LNC of the former was lower than the latter.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Study of a semi-arid grassland revealed that the stem-leaf biomass ratio is more responsive to grazing, while the specific leaf area is more sensitive to N enrichment (Zheng et al, 2022). Further investigations have indicated that the addition of N has a negative effect on the leaf dry matter content (Mao et al, 2014;Zheng et al, 2017;Sun et al, 2022). However, there is no consensus on the responses of specific leaf area, leaf P and N concentrations to N addition between different species (Huang et al, 2008;Zhang et al, 2018;Su et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As plant economic spectrum predicts, species with the traits capable of acquiring resource rapidly (e.g., high N concentration, specific leaf area, and photosynthetic rate) would compete for resource more strongly under N enrichment ( Wright et al, 2004 ; La Pierre and Smith, 2015 ). Recent studies have revealed inconsistent responses of plant functional traits to nutrient addition, while some studies showed that N addition enhanced leaf N concentration, chlorophyll concentration and specific leaf area, thus leading to a marked increase in photosynthetic rates ( Tatarko and Knops, 2018 ; Zheng et al, 2018 ; Sun et al, 2022 ). Others found no effect of N addition on leaf mass area, area-based concentrations of foliar N and chlorophyll concentrations ( Hu and Wan, 2019 ).…”
Section: Introductionmentioning
confidence: 99%